(untitled) (Bangladesh Journal of Pharmacology, 2013)
Most of the species of Buddleja have found applications in folk medicine. This study aimed to evaluate the in vitro antimicrobial and cytotoxic potentials of B. polystachya extracts. Four extracts were prepared A-D (dichloromethane, ethyl acetate, n-butanol, and aqueous extracts, respectively). The antimicrobial activity was evaluated using the broth micro-dilution assay for minimum inhibitory concentrations (MIC). The crystal violet staining method (CVS) was used for the evaluation of the cytotoxic activity on HepG-2, MCF-7 and HCT-116 human cell lines. Results showed that the highest antimicrobial activity was given by the ethyl acetate extract followed by the dichloromethane extract, while the n-butanol revealed moderate activity against gram positive bacteria only with no activity against the rest of tested microorganisms. The aqueous extract was totally ineffective against all tested microorganisms at 20 mg/ml. Among the four extracts tested, dichloromethane and ethyl acetate extracts showed the highest cytotoxic activity on all three human cell lines.